Inhibiting STAT3 in a murine model of human breast cancer-induced bone pain delays the onset of nociception. (January 2019) - Linher-Melville, Katja; Sharma, Manu; Nakhla, Peter; Kum, Elena; Ungard, Robert; Park, Ji; Rosa, David; Gunning, Patrick; Singh, Gurmit
Aggressive breast cancer subtypes utilize system xc −, a membrane antiporter, to import cystine for glutathione synthesis and maintenance of redox homeostasis, in turn releasing glutamate as a metabolic pro-nociceptive by-product. Metastatic breast cancers establish themselves at distal sites including bone, where changes in extracellular glutamate levels contribute to cancer-induced bone pain. We previously established that stearically blocking system xc − activity with sulfasalazine delays the onset of nociceptive behaviours and that xCT, the functional antiporter subunit, is positively regulated by signal transducer and activator of transcription 3 (STAT3). In the current investigation, a murine xenograft cancer-induced bone pain model was applied to examine whether pharmacological inhibition of phosphorylated STAT3 (pSTAT3) induces changes in nociception. A high glutamate-releasing, xCT/pSTAT3 over-expressing human breast cancer cell line was selected for injection into the distal epiphysis of the right femur of female nude mice. A 14-day regimen of intraperitoneal injections with either vehicle or the novel STAT3 inhibitor DR-1–55 commenced three weeks after initial intrafemoral bone injection. Nociceptive behaviours were temporally monitored by automated von Frey, dynamic weight bearing and open-field testing for the duration of the study, beginning at the baseline. Prior to sacrifice and at ethical end point, tumour-induced osteolytic lesions were radiographically assessed. Treatment with DR-1–55 significantly delayed the onset and severity of spontaneous and induced nociceptive behaviours, also decreasing human SLC7A11 ( xCT ) mRNA levels in tumour-bearing limbs without altering osteolysis. In addition, two pro-inflammatory cytokines released by this cell line, interleukin 6 and interleukin 1β, were also down-regulated at the mRNA level in response to DR-1–55 treatment in vivo, with lower human interleukin 6 levels detected in the host circulation. This study demonstrates that targeting pSTAT3 may be a viable therapeutic means to manage cancer-induced bone pain, alone or in combination with stearic system xc − blockers.